A Bibliometric Analysis of 100 Most-Cited Articles on Corneal Cross-Linking - Yang, Kaili; Xu, Liyan; Wang, Shaopei; Zhu, Meng; Fan, Qi; Gu, Yuwei; Wang, Yawen; Wang, Qing; Zhao, Dongqing; Pang, Chenjiu; Ren, Shengwei (Frontiers in Medicine, 2022)
Background Highly cited papers are expected to have high-quality data that significantly contribute to the body of knowledge. The study aimed to evaluate the characters of the 100 most-cited articles on corneal cross-linking (CXL) through a bibliometric analysis. Materials and Methods The Web of Science database was searched to identify papers published from 1950 to 2020. A bibliometric analysis of the top 100-cited articles was conducted in the current study. The citation differences between basic research, clinical research, and reviews were compared by Kruskal–Wallis test. The association between citations and publication year was evaluated by Spearman correlation analysis. The VOSviewer software was used to create networks of co-authorship and keywords map. Results The median values of the number of citations, citations/year since publication, and citations since 2013 were 101, 9.5, and 11.92, respectively. A total of 61% of articles were clinical research. The citations since 2013 of clinical research were lower than basic research and the reviews (all p < 0.001). The publication year was positively correlated with the number of publications (r = 0.665, p = 0.013), and the total number of citations decreased for basic research (r = –0.447, p = 0.017), and clinical research (r = –0.433, p < 0.001). The J REFRACT SURG publishes the highest number of articles. The corresponding authors were predominantly from the Italy (N = 17), Germany (N = 16), and United States (N = 15). Spoerl Eberhard has the highest number of citations and total link strength with 15 articles. Extensive collaboration existed among the main core nodes containing “cross-linking (N = 45),” “riboflavin (N = 44),” and “ultraviolet A (UVA) (N = 42).” Conclusion The present study focused on the comprehensive analysis of the top 100-cited articles on the CXL research, providing insight into research developments over the past decades.